Basic documents of South Asian Regional Cooperation : SARC participating countries, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, Sri Lanka (Issued by Conference Cell, Ministry of External Affairs, 1983)
Comprises reports of the Committee of the Whole and joint communiques issued at the conclusion of various meetings of foreign secretaries of South Asian countries.